DSGE 모형을 이용한 추세와 경기순환변동분의 분해 - 황영진 (12711, 2012)
This paper decomposes and estimates trend/cyclical components of some key macro variables?GDP, inflation, and interest rate, using a simple DSGE model along with flexible trend specification. The extracted cyclical components of output and interest rate a